State of Gender Diversity and Equity Policies within Plastic and Reconstructive Surgery in Canada - Retrouvey, Helene (Plast Reconstr Surg Glob Open, 2020)
BACKGROUND: Given the growing number of women in plastic and reconstructive surgery (PRS), it is imperative to evaluate the extent of gender diversity and equity policies among Canadian PRS programs to support female trainees and staff surgeons. METHODS: A modified version of the United Nations Women’s Empowerment Principles (WEPs) Gender Gap Analysis tool was delivered to Canadian PRS Division Chairs (n = 11) and Residency Program Directors (n = 11). The survey assessed gender discrimination and equity policies, paid parental leave policies, and support for work/life balance. RESULTS: Six Program Directors (55% response rate) and ten Division Chairs (91% response rate) completed the survey. Fifty percent of respondents reported having a formal gender non-discrimination and equal opportunity policy in their program or division. Eighty-three percent of PRS residency programs offered paid maternity/paternity/caregiver leave; however, only 29% offered financial or non-financial support to its staff surgeons. Only 33% of programs had approaches to support residents as parents and/or caregivers upon return to work. Work/life balance was supported for most trainees (67%) but only few faculty members (14%). CONCLUSIONS: The majority of Canadian PRS programs have approaches rather than formal policies to ensure gender non-discrimination and equal opportunity among residents and faculty. Although residency programs support wellness, few have approaches for trainees as parents and/or caregivers upon return to work. At the faculty level, approaches and policies lack support for maternity/paternity/caregiver leave or work/life balance. This information can be used to develop policy for support of plastic surgery trainees and faculty.